Um ambiente integrado para manipulação de tráfego multicast - Lima, Weldson Queiroz de (2004)
In the two last decades of the past century, following the consolidation of the Internet as the world-wide computer network, applications generating more robust data flows started to appear. The increasing use of videoconferencing stimulated the creation of a new form of point-to-multipoint transmission called IP Multicast. All companies working in the area of software and the hardware development for network videoconferencing have adjusted their products as well as developed new solutionsfor the use of multicast. However the configuration of such different solutions is not easy done, moreover when changes in the operational system are also requirede. Besides, the existing free tools have limited functions, and the current comercial solutions are heavily dependent on specific platforms. Along with the maturity of IP Multicast technology and with its inclusion in all the current operational systems, the object-oriented programming languages had developed classes able to handle multicast traflic. So, with the help of Java APIs for network, data bases and hipertext, it became possible to the develop an Integrated Environment able to handle multicast traffic, which is the major objective of this work. This document describes the implementation of the above mentioned environment, which provides many functions to use and manage multicast traffic, functions which existed only in a limited way and just in few tools, normally the comercial ones. This environment is useful to different kinds of users, so that it can be used by common users, who want to join multimedia Internet sessions, as well as more advenced users such engineers and network administrators who may need to monitor and handle multicast traffic